Emancipation from the Whirlwind: Piety and Rebellion among Jewish-American Post-Holocaust and Christian Liberation Readings of Job - Tollerton, David C. (Studies in Christian-Jewish relations, 2008)
This article focuses upon the manner in which the Book of Job’s dissonant messages of theological radicalism and conservatism have been utilised within discussion of two specific episodes of innocent suffering in the modern world - the murder of six million Jews during the Holocaust and the suffering of the oppressed in the developing world. Overlaying the discussion, the following model is proposed: that, firstly, Christian liberation theologians emphasise the more theologically conservative messages that can be drawn from Job while asserting radical political opposition to those who possess power. Conversely, Jewish Holocaust theologians empathise with Job’s more theologically radical elements, yet do so within outlooks committed to conservatively maintaining the security and power of the state of Israel after two thousand years of Jewish powerlessness. This model is tested by focusing upon seven treatments of Job associated with liberation or Holocaust theologies. It is concluded that, although there are significant complications, in broad terms the model largely holds " offering a comparative insight into contextual Christian and Jewish interpretations of the Bible in which political radicalism and theological radicalism are found to be at odds with one another.